Silaturahmi Sebagai Sarana Komunikasi Interpersonal Dalam Mempererat Hubungan Sosial (Perspektif Hadits) - Safrizal, Safrizal (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2025)
Silaturahmi, as a tradition developed in various cultures, has a very important role in strengthening social relationships. In the Indonesian context, silaturahmi is not only seen as a social gathering, but also as a form of interpersonal communication that strengthens the bonds between individuals within a family, community, or wider society. This article aims to explore silaturahmi as a means of interpersonal communication, as well as its impact on the quality of social relationships in society. This research uses a qualitative approach with interviews and participatory observation of individuals involved in silaturahmi activities in various communities. The results show that silaturahmi provides an opportunity to exchange information, deepen emotional relationships, and create a sense of togetherness that increases social solidarity.